Cyberbullying through intellect - related insults - Shahidatul Maslina Mat Sood,; Tan, Kim Hua; Bahiyah Abdul Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Unrestricted utilisation of digital devices and online platforms promulgates cyberbullying, which has been typically identified with the presence of potentially profane or offensive words that can cause aggravation to others. Previous studies have clarified that certain challenges arise in detecting abusive language in social media, especially on Twitter. The apparent reason for such encounters is typically triggered by the informal language used in various tweets. This study discusses the issues of abusive language that are used in Malaysian’s online communication by highlighting the linguistic features of aggressive insulting words used by social media users in nit-picking an individual’s intelligence. Data collection and analysis are conducted in two stages. Firstly, a self-constructed questionnaire is conducted to elicit imperative keywords or phrases used in assisting subsequent analysis of the content-based approach. Secondly, Twitter data, which have been streamed using the Twitter API and R statistical software, are explored. Thematic analysis is also used in the second phase to analyse the keywords that are subjected to qualitative explanations. Initial results indicate ‘bodoh’ as the most common online insult used to degrade an individual’s intelligence. Twitter users also make use of more abusive words (insults) in Malay than in English for degrading purposes through a variety of intelligence-related insults such as ‘bebal’, ‘sengal’, ‘gila’, ‘bodoh’, ‘bangang’, ‘bengap’, ‘semak’ and ‘bongok’. Likewise, linguistics realisations such as spelling alteration, word repetition, laughing remarks, punctuations, animal imagery, dialect interference, code-mixing, and Malaysian English markers are observed through the features of those highlighted insults.